Les « Entretiens du patrimoine » (1988-2001) ou la « grand-messe » des professionnels du patrimoine - Cécile Lestienne (In Situ)
In 1987, the Minister of Culture, François Léotard, announced the creation of the ‘Entretiens du patrimoine’, annual ‘conversations’ bringing together heritage professionals and, in particular, since 1994, academics and intellectuals from the humanities, in order to discuss issues raised by the conservation and the identification of the heritage. Lasting two or three days on average, these meetings took place in different provincial towns between 1988 and 1993, then in Paris from 1994 to 2001. The proceedings of the lectures and debates were published from 1988 to 1993 as 'Actes des colloques de la Direction du patrimoine', then, from 1994 onwards, under the series title of 'Actes des Entretiens du patrimoine'. Initially designed as a ‘tool’ for professional training, these ‘Entretiens’ have evolved, since 1994, into a public forum were notions of heritage are debated and theorised.